The Effect of Grit, Proactive Personality, Supervisor Support, Organizational Support on Employee Work Engagement - Ingarianti, Tri Muji; Panggabean, Aninda Namira; Khotimah, Khusnul; Silfiasari, Silfiasari (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2024)
Each employee may have different level of work engagement. A company must wants its employees to have high level of work engagement so they can work vigorously, with good dedication and get fully immersed in the work. The grit, proactive personality, supervisor support and organizational support factors can be predicted to to be able to influence work engagement of the employees. This study aims to discover the effect of grit, proactive personality, supervisor support, and organizational support on work engagement on employees. The subject of this study was employees who work at companies in East Java. Quantitative method was applied in this study with 197 subjects in total using simple random sampling technique. Grit Scale, Proactive Personality Scale (PPS), Surveys of Perceived Supervisor Support, Perceived Organizational Support (POS), and Utrech Work Engagement Scale - 9 (UWES-9) were the instruments used in this study. The results of the analysis explain there was an effect of grit on work engagement on employees (p<.05), there was an effect of supervisor support on work engagement on employees (p<.05), there was an effect of organization support on work engagement on employees (p<.05), and there wasn’t an effect of proactive personality on work engagement on employees (p>.05). As for suggestions for further research, paying more attention to completeness and suitability when distributing questionnaires to respondent, and it is necessary to pay more attention to the characteristics of the research subjects and other factors that might affect employee engagement such as social welfare, quality of work life, and organizational culture.